Cardiac responses to progressive upright exercise in adult male cyclists - Rowland, T. W.; Roti, M. W. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: Previous investigations have indicated that maximal stroke volume is the primary factor which differentiates physiological aerobic fitness (VO2max) in endurance athletes from nonathletes. Understanding the pattern of stroke volume response to progressive exercise may provide insights into the mechanisms which are responsible for this difference. METHODS: Doppler echocardiography was used to estimate stroke volume changes with maximal upright cycle exercise in 8 highly trained adult cyclists (mean age 30.5+/-1.6 years) and 16 age-matched nontrained males. Ventricular dimensions were measured during exercise using 2-dimensional echocardiography (parastemal long axis view). Findings were compared to a group of untrained adult male subjects. RESULTS: Mean maximal oxygen uptake was 73.7+/-7.0 and 47.4+/-7.5 ml x kg(-1) x min(-1) in the 2 groups, respectively. Stroke volume rose in both the cyclists and nontrained subjects at the onset of exercise but then plateaued without significant change to exhaustion. Values for stroke index were significantly greater at rest and all levels of exercise in the cyclists (maximal 85+/-13 versus 61+/-13 ml x m(-2)). Two dimensional echocardiograms during exercise in the cyclists revealed a small initial rise in left ventricular end-diastolic dimension and then a small decline, while systolic dimension decreased progressively, resulting in a rise in shortening fraction. CONCLUSION: These findings are consistent with the concept that determinants of stroke volume at rest are most influential in defining differences in maximal stroke volume between athletes and nonathletes.